KARATERISTIK PEMBIAYAAN SYARIAH DAN KELEMBAGAAN USAHA TERHADAP PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH DI KOTA PADANG - Neng Kamarni; Amra Ausri (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2015)
This research aimed to analyze the role of Islamic finance gained SMEs, institutional characteristics of the business and the characteristics of entrepreneurs to the development of Micro, Small, and Medium Enterprises in the city of Padang. The study design used descriptive approach qualitative and quantitative descriptive. Data were analyzed using analysis Crosstabulation and Chi-Square, a descriptive analysis technique.Crosstabulation based analysis and Chi-Square test, there is a significant relationship between the amount of financing, education, length of business, business development training, and the legality of the increase in revenue SMEs. While there was no significant relationship between the type of business and the ownership of the financial statements with a revenue increase of SMEs. SME revenue improvement opportunities are greatest in terms of the amount of financing. Of the 82% who obtain financing on Rp.5.000.000, 61% of SMEs could increase his income. The second biggest opportunities is occupied by SMEs that have financial statements, as many as 58% of the 84 respondents who had had financial reports may increase their income.Keyword : islamic finance, institutioal charateristics